Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik Pada Bumdes: Literatur Review - Gustaf Ikhsan Romadhoni (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This research aims to determine the application of Financial Accounting Standards (SAK) for Entities Without Public Accountability (ETAP) in BUMDes so that they can present accurate financial reports. The research method used is Literature Review (LR). This research uses data from journals that are available in full text form. The research results show that there are still many BUMDes that cannot present financial reports in accordance with SAK ETAP. This is due to a lack of understanding by the management running BUMDes regarding SAK ETAP.